Embodiment as a Paradigm for Understanding and Treating SE-AN: Locating the Self in Culture - Musolino, Connie Marguerite; Warin, Megan; Gilchrist, Peter (Frontiers in Psychiatry, 2020)
There has been a growing call for sociologically engaged research to better understand the complex processes underpinning Severe and Enduring Anorexia Nervosa (SE-AN). Based on a qualitative study with women in Adelaide, South Australia who were reluctant to seek help for their disordered eating practices, this paper draws on anthropological concepts of embodiment to examine how SE-AN is experienced as culturally grounded. We argue that experiences of SE-AN are culturally informed, and in turn, inform bodily perception and practice in the world. Over time, everyday rituals and routines became part of participants’ habitus’, experienced as taken-for-granted practices that structured life-worlds. Here, culture and self are not separate, but intimately entangled in and through embodiment. Approaching SE-AN through a paradigm of embodiment has important implications for therapeutic models that attempt to move anorexia nervosa away from the body and separate it from the self in order to achieve recovery. Separating experiences—literally disembodying anorexia nervosa—was described by participants as more than the loss of an identity; it would dismantle their sense of being-in-the-world. Understanding how SE-AN is itself a structure that structures every aspect of daily life, helps us to understand the fear of living differently, and the safety that embodied routines bring. We conclude by asking what therapeutic treatment might look like if we took embodiment as one orientation to SE-AN, and focused on quality of life and harm minimization.